Isolation, Identification and Assessment of Efficient Cellulase Producing Bacteria from the Termite Guts - Sirikhwan Tinrat; Lueacha Tabtimmai; Saranya Sedtananun; Chakrit Tachaapaikoon; Kiattawee Choowongkomon (HAYATI Journal of Biosciences, 2024)
The present study is concerned with the screening the cellulase-producing bacteria from termite gut, assessed potential cellulase-producing bacteria and partial characterization (optimum parameters) of cellulase from isolated bacteria. The result showed that 15 out of 48 isolated strains was positive for degrading the carboxy methyl cellulose (CMC) in agar by congo-red method. After screening by DNS assay, three selected bacteria exhibited high cellulase activity that were identified as Citrobacter amalonaticus CM 1-3, Bacillus cereus CM 5-1 and Streptococcus salivarius CE 5-1 using 16S rRNA sequence analysis. All bacterial strains utilized CMC and showed the highest cellulase activity. Cellulase characterization of C. amalonaticus CM 1-3 and S. salivarius CE 5-1 was revealed optimum activity at 35°C, pH 7.0 and for 48 h. Bacillus cereus CM 5-1 represented its potential use in industrial processes due to thermostable cellulase production. The crude cellulase of this strain was purified by (NH4)2SO4 precipitation with 1.58 purification fold and 74.38% overall recovery. The optimal temperature and pH for cellulase activity of B. cereus CM 5-1 were at 40°C and pH 7.0. Thus, this study provided additional information about the diversity and partial characteristic cellulase of cellulolytic bacteria from termite gut for future industrial applications.